PENGARUH eWOM (ELECTRONIC WORD OF MOUTH) PADA MEDIA SOSIAL FACEBOOK TERHADAP MINAT BELI KONSUMEN (STUDI PADA TEBING BAR & CAFE) - Adrian Gae Lomi; Abas Kasim; Juita L.D. Bessie (Journal of Management Small and Medium Enterprises (SMEs), 2016)
The purposes of this study was to determine the effect eWOM (electronic word of mouth), whichconsists of Platform Assistance, Concern for Others, Expressing Positive Feelings, and Helping theCompany on social media Facebook, partially and simultaneously on Consumer Buying Interest.The object of research is the Tebing Bar & Cafe in Yos Sudarso Kota Kupang. The independentvariables are the Platform Assistance, Concern for Others, Expressing Positive Feelings, andHelping the Company. The population in this study are active Facebook users who have beenexposed to information about Tebing Bar and Cafe on Facebook. Samples taken as many as 50respondents using purposive sampling technique. Then, analysis of data obtained by using multipleregression analysis. This analysis includes: multiple analysis test, classic assumption test,hypothesis testing through F-test and t-test, and analysis of the coefficient of determination (R2).Based on the research results, obtained the regression equation: Y = -2.385 + 0.612X1+ 0.176X2+ 0.405X3+ 0.271X4. Based on statistical data analysis, the classic assumption test, regressionmodel to be free and normal distribution. Individually from each of the most influential variable isthe variable Platform Assistance with a regression coefficient of 0.612, followed by a variableExpressing Positive Feelings with a regression coefficient of 0.405, variable Helping the Companywith a regression coefficient of 0.271 and a variable Concern for Others with a regression coefficientof 0.176. Hypothesis testing using t-test showed that the four independent variables are all proven tosignificantly affect the dependent variable Consumer Buying Interests, whereas through F-test canbe seen that the independent variable is indeed feasible to test the dependent variable ConsumerBuying Interests. Figures Adjust R-Square of 0.948 indicates that 94.8% of the variable ConsumersBuying Interest are influenced by independent variables in the regression equation. While theremaining 5.2% variable Consumer Buying Interest are influenced by other variables that are notdiscussed this research.Keywords: Electronic Word of Mouth (e-WOM), Consumer Buying Interest